The State of Intermediate Clinical Endpoints as Surrogates for Overall Survival in Prostate Cancer in 2024 - Miszczyk, Marcin; Rajwa, Paweł; Fazekas, Tamás; Briganti, Alberto; Karakiewicz, Pierre I; Rouprêt, Morgan; Shariat, Shahrokh F (European urology oncology, 2024)
In the past, selection of intermediate clinical endpoints (ICEs) in prostate cancer (PCa) trials largely depended on qualitative assessments; however, the advancing quality of research necessitates a robust correlation with overall survival (OS). This review summarises the results from several high-quality meta-analyses that explored the validity of ICEs as surrogates for OS. We found strong evidence that metastasis-free survival can serve as an ICE in localized PCa. In advanced disease, valid ICEs were identified only within the context of metastatic hormone-sensitive PCa, including radiological and clinical progression-free survival; however, concerns remain regarding their use owing to the limited generalisability of the data used to validate their surrogacy. PATIENT SUMMARY: Intermediate clinical endpoints can reduce the costs of trials and allow earlier introduction of new treatment methods. This article summarises results from studies verifying the validity of these endpoints as surrogates for overall survival.
Keywords: Prostatic Neoplasms; Event-free survival; stanovení cílového parametru; nádory prostaty; Humans; míra přežití; Local failure; mužské pohlaví; Male; lidé; Endpoint Determination; Biochemical failure; Clinical failure; Disease-free survival; Survival Rate